Scaled Quail Reproduction in the Trans-Pecos Region of Texas - Robert J. Buntyn; Eddie K. Lyons; Dale Rollins; Kenneth A. Cearley (National Quail Symposium Proceedings, 2017)
Scaled quail (Callipepla squamata) populations have declined markedly throughout their range. We monitored hatch rates and nest placement of radio-marked female scaled quail (n 1⁄4 210) in Pecos County, Texas relative to the availability and location of ‘spreader dams’ (i.e., shallow water catchments) through the nesting seasons of 1999 and 2000. Hatch rates were high both years (i.e., 67 and 84% for 1999 and 2000, respectively). The predominant nesting microhabitat was tobosa (Pleuraphis mutica), which accounted for 85% of the nests located. We failed to document any direct impacts of spreader dams on nesting ecology of scaled quail.
Keywords: Callipepla squamata; Chihuahuan desert; reproduction; scaled quail; Trans-Pecos; Texas